A Systematic Review of Patient-Reported Outcomes to Inform Women's Health Quality Improvement [A304]. (May 2022) - Ling, Vivian; Kang, Minji M.; Nguyen, Buu-Hac; McGowan, Makazhia; Peahl, Alex F.; Moniz, Michelle
Abstract : INTRODUCTION: Patient-reported outcomes (PROs) are defined as data reported from patients without interpretation or alteration from others. Use of PROs in health care can identify opportunities for quality improvement (QI) that may be overlooked by clinician-based metrics. This rapid review evaluated best practices for selecting, implementing, and utilizing PROs to inform QI initiatives. METHODS: We performed a systematic review of studies addressing PROs in PubMed and Google Scholar. Inclusion criteria specified use of PROs in a health care setting for QI. We excluded articles where PROs were utilized only as an outcome. Further evaluation was based on the PICOS (Population, Intervention, Comparator, Outcomes, Setting) framework. Two members of the study team independently reviewed articles for inclusion and data abstraction. RESULTS: A total of 156 articles were independently reviewed: 111 were removed following title and abstract screening, and 21 after full-text assessment, resulting in 24 articles for qualitative synthesis. The most common populations were clinical trial participants (46%), patients with cancer (16.7%), and postpartum patients (8.3%). Articles revealed key considerations for integrating PROs in QI work, including: 1) selection (e.g., use of specific criteria, expert or literature review), 2) implementation (e.g., data management, survey use), and 3) utilization (e.g., for decision-making, future PRO selection). CONCLUSION: This review highlights several important steps in effective integration of PROs in QI initiatives, including selection, implementation, and application. Future work is needed to define best practices for incorporating these principles in quality initiatives to improve patient-centeredness and equity among diverse populations.